Improving Students' Conceptual Understanding with Problem-Based Learning in Islamic Education at SD Negeri 106218 Pematang Toba - Arifah; Nurhabibi; Sofia, Nida Aya (Jurnal Pendidikan Profesi Guru, 2023)
This study aims to improve students' Concept Understanding in Islamic Education by using the Problem-Based Learning Model. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data of this study were obtained by test and observation techniques. Tests are used to improve students' understanding and observations are used to analyze teacher and student learning activities. The data analysis technique used in this study is descriptive statistics by comparing the results obtained with indicators of research success. The results of the study indicate that learning using the Problem-Based Learning Model can improve students' conceptual understanding. This can be seen from the increase in the percentage of completeness of improving students' conceptual understanding in each cycle with details of the pre-cycle 46.56%, the first cycle 77.57% and in the second cycle increased to 89.77%. Thus, the use of the Problem-Based Learning Model can be used as an alternative to improve student learning outcomes.